Doxorubicin plus lurbinectedin in patients with advanced endometrial cancer: results from an expanded phase I study. Issue 11 (5th October 2021) - Kristeleit, Rebecca; Moreno, Victor; Boni, Valentina; Guerra, Eva M; Kahatt, Carmen; Romero, Ignacio; Calvo, Emiliano; Basté, Neus; López-Vilariño, José A; Siguero, Mariano; Alfaro, Vicente; Zeaiter, Ali; et al.
Abstract : Objective: Second-line treatment of endometrial cancer is an unmet medical need. We conducted a phase I study evaluating lurbinectedin and doxorubicin intravenously every 3 weeks in patients with solid tumors. The aim of this study was to characterise the efficacy and safety of lurbinectedin and doxorubicin for patients with endometrial cancer. Methods: Thirty-four patients were treated: 15 patients in the escalation phase (doxorubicin 50 mg/m 2 and lurbinectedin 3.0–5.0 mg) and 19 patients in the expansion cohort (doxorubicin 40 mg/m 2 and lurbinectedin 2.0 mg/m 2 ). All histological subtypes were eligible and patients had received one to two prior lines of chemotherapy for advanced disease. Antitumor activity was evaluated every two cycles according to the Response Evaluation Criteria in Solid Tumors version 1.1. Adverse events were graded according to the National Cancer Institute-Common Terminology Criteria for Adverse Events version 4. Results: Median age (range) was 65 (51–78) years. Eastern Cooperative Oncology Group performance status was up to 1 in 97% of patients. In the escalation phase, 4 (26.7%) of 15 patients had confirmed response: two complete and two partial responses (95% CI 7.8% to 55.1%). Median duration of response was 19.5 months. Median progression-free survival was 7.3 (2.5 to 10.1) months. In the expansion cohort, confirmed partial response was reported in 8 (42.1%) of 19 patients (95% CI 20.3% to 66.5%). Median duration of response was 7.5 (6.4 to not reached) months, median progression-free survival was 7.7 (2.0 to 16.7) months and median overall survival was 14.2 (4.5 to not reached) months. Fatigue (26.3% of patients), and transient and reversible myelosuppression (neutropenia, 78.9%; febrile neutropenia, 21.1%; thrombocytopenia, 15.8%) were the main grade 3 and higher toxicities in the expanded cohort. Conclusions: In patients with recurrent advanced endometrial cancer treated with doxorubicin and lurbinectedin, response rates (42%) and duration of response (7.5 months) were favorable. Further evaluation of doxorubicin and lurbinectedin is warranted in this patient population.